A multi-year injury epidemiology analysis of an elite national junior tennis program. Issue 1 (January 2019) - Gescheit, Danielle T.; Cormack, Stuart J.; Duffield, Rob; Kovalchik, Stephanie; Wood, Tim O.; Omizzolo, Melanie; Reid, Machar
Abstract: Objectives: To profile multi-year injury incidence and severity trends in elite junior tennis players from a national program. Design: Prospective cohort. Methods: Injury data was collated by sex, age and region for all nationally-supported Australian junior players (58m, 43f 13–18y) between 2012–2016. Injury was defined as a physical complaint from training/matchplay interrupting training/matchplay determined by presiding physiotherapists and doctors. Severity represented the days of interrupted training/matchplay per injury. Injury incidence was reported per 1000 exposure hours. Incidence rate change and rate ratios (RR) ±95% confidence intervals were used to assess changes over time. Results: No difference in male and female injury incidence existed (2.7 ± 0.0 v 2.8 ± 0.0) yet male injuries were more severe (3.6 ± 0.6 v 1.1 ± 0.9 days). The lumbar spine was the most commonly and severely injured region in both sexes (4.3 ± 0.2, 9.9 ± 1.4 d). Shoulder injuries were the second most common in both sexes (3.1 ± 0.2) and with the second highest severity in males (7.3 ± 1.4d). Knee injuries were also common in males (2.3 ± 0.2) yet potentially reduced over time (0.4 ± 0.6 RR) as pelvis/buttock injuries increased (3.4 ± 14.0 RR). Females had high trunk and abdominal injury incidences (2.5 ± 0.3). Independent of sex, the injury incidence increased with age from 2.0 ± 0.1 (13y) to 2.9 ± 0.1 (18y). Conclusions: Despite no sex-based difference in injury incidence, male injuries resulted in more interrupted days of training/matchplay. The lumbar spine and shoulder were the most commonly injured body regions in both sexes. The number of injuries sustained by players also increased as they aged.